Comparison between Unitary and Federal System - Kandel , Ishwari Prasad (HISAN: Journal of History Association of Nepal, 2024)
The title 'Comparison between Unitary and Federal System' is the focus research topic for the critical analysis of the Comparative Politics or political race to sustain in the lens of unitary and federal systems. The objective of this research is to generate a political ideology based on the unitary and federal system and its base foundation and fundamental understanding of politics. To conduct this research in terms of methodological paradigm. Where, the secondary data and information have been taken from the various scholarly works, based on Unitary and Federal, such as the different forms of unitary and federal systems based on their origin, design and jurisdiction and the types of government and constitution. There are many merits and demerits of unitary government. It is useful in the term that rules and regulations in this government system remain consistent and equal throughout the country